Techno-economic analysis of different microgrid energy management strategies - Su, Tianyi (Nanyang Technological University, 2022)
Solar energy is the most commonly used renewable energy in Singapore. Recent development of variable renewable energy raises concerns about the performance and reliability of the power system. Since solar energy is intermittent and inefficient, two important factors need to be considered when it connects with the power grid. One is power system stability, and another is the output power from photovoltaic (PV) cells. For maintaining grid voltage stability and maximizing PV output power, different control strategies are implemented in a modeled on-grid PV system in PLECS and MATLAB. The performance of P&O and IC MPPT control algorithms are compared and the performance of no feedback control and dual-loop control of converter are compared in this dissertation. This modeled PV system can also be established in HOMER to assess the optimization results based on the chosen load profiles, local temperature and irradiance data. Technical and economic performances of the system are compared according to HOMER simulation results which provide an electrical overview of total energy production and consumption and an economic overview of net present cost (NPC), cost of energy (COE), operational cost and capital cost of electrical energy. The optimal size of PV strings can be obtained by HOMER optimization results.